Answer:
single solution : (4 ; 6)
Step-by-step explanation:
hello :
4x-y=10.....(1)
y=2x-2.....(2)
put the value for y in (1) :
4x-(2x-2)=10
4x-2x +2 = 10
2x=8
x=8/2 =4
but : y = 2x-2
so : y =2(4)-2=6
single solution : (4 ; 6)
It’s the last one because you have a coupon which means your subtracting
Answer:
C) 14
Step-by-step explanation:
3x-6=36
3x=36+6
3x=42
x=42/3
x=14
Answer:
<u>y=5/2x+13.5</u>
Step-by-step explanation:
5x-2y=10
-2y=-5x+10
y= 5/2x-5
y-6=5/2(x+3)
y-6=5/2x+ 7.5
<u>y=5/2x+13.5</u>
Answer:
Step-by-step explanation:
Let T represent the total amount spent.
The word and implies addition so the equation would be T= 2.75g+3.35c .
Now plug in the g and c values given in part b
So T= 2.75(5.8)+3.35(6)
Next simplify the expression
This is what T or the total Spent equals